The magnitude of oral rehydration salt utilization in diarrhea hot spot regions of Ethiopia and its associated factors among under-five children: A multilevel analysis based on Bayesian approach - Negesse, Yilkal; Fetene Abebe, Gossa; Addisu, Abebaw; Setegn Alie, Melsew; Alemayehu, Dereje (Frontiers in Public Health, 2022)
Background Diarrhea leads the children to severe dehydration or death as a result of the loss of water and electrolytes (namely, potassium, chloride, sodium, and bicarbonate). To compensate for the losses, ORS is given to children who experienced diarrhea. Objective To estimate the magnitude of ORS utilization in diarrhea hotspot regions of Ethiopia and to assess its associated factors among under-five children. Methods To conduct this study, we used the 2016 Ethiopian demographic and health survey data. A total of 1,079 weighted sample children were selected. Each sample was selected randomly. Then, to identify factors associated with ORS utilization in diarrhea hotspot regions of Ethiopia, a multilevel analysis based on the Bayesian approach was applied. Finally, the credible interval of AOR that does not include 1 was considered statistically significant. Results The magnitude of ORS utilization for children in diarrhea hotspot regions of Ethiopia was 28%. Being urban resident (AOR = 1.92; 95% CrI: 1.13–3.3), woman household head (AOR = 2.11; 95% CrI: 1.3–3.9), having higher educational level (AOR = 1.52; 95% CrI: 1.04–2.22), member of health insurance (AOR = 1.73; 95% CrI: 1.14–2.43), and being exposed for media (AOR = 1.43; 95% CrI: 1.18–2.5) increases ORS utilization for diarrhea management. Conclusion Residence, educational level, health insurance, and media exposure were the factors of ORS utilization. So, to increase the practice of ORS utilization for diarrhea management in Ethiopia, the Ministry of Health and the Government of Ethiopia should consider those factors when they design diarrhea prevention and control strategies.